2012
DOI: 10.1007/s13762-012-0120-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sludge pretreatment on sludge reduction in a lab-scale anaerobic/anoxic/oxic system treating domestic wastewater

Abstract: Excess sludge disposal is one of the serious challenges in biological wastewater treatment. Reduction of sludge production would be an ideal way to solve sludgeassociated problems rather than the post-treatment of the sludge produced. In this study, a new wastewater treatment process combining anaerobic/anoxic/oxic system with thermochemical sludge pretreatment was tested in a laboratory scale experiment. In this study, the effects of the sludge pretreatment on the excess sludge production in anaerobic/anoxic/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In contrast to the S S fraction, the actual role of slowly biodegradable compounds has not been ultimately recognized in terms of both theoretical aspects (mechanism of utilization) and practical aspects (influence on process performance). In the traditional opinion, these compounds become available for utilization by microorganisms after rapid enmeshment into sludge flocs and follow-up hydrolysis to the readily biodegradable substrate (Henze et al 1987;Melcer et al 2003;Uan et al 2013). The latter process is accomplished by heterotrophic microorganisms, which release extracellular enzymes that break down and solubilize polymers, such as proteins, lipids and polysugars.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the S S fraction, the actual role of slowly biodegradable compounds has not been ultimately recognized in terms of both theoretical aspects (mechanism of utilization) and practical aspects (influence on process performance). In the traditional opinion, these compounds become available for utilization by microorganisms after rapid enmeshment into sludge flocs and follow-up hydrolysis to the readily biodegradable substrate (Henze et al 1987;Melcer et al 2003;Uan et al 2013). The latter process is accomplished by heterotrophic microorganisms, which release extracellular enzymes that break down and solubilize polymers, such as proteins, lipids and polysugars.…”
Section: Introductionmentioning
confidence: 99%
“…Since Morgenroth et al (1997) found the aerobic sludge granulation in a sequence bioreactor, researchers have conducted numerous studies on the formation and characteristics of aerobic granule, affecting factors of sludge granulation, mass transfer and model simulation, extracellular polymeric substances (EPS), and formation mechanism (Beun et al 2002;Liu et al 2006;Wan et al 2009;de Kreuk et al 2010;Ni and Yu 2010;Gao et al 2011, Uan et al 2013. However, the aerobic granular sludge system is still not stable, and the application of this technology is faced with big bottlenecks and challenges (Winkler et al 2011;Chen et al 2007;Adav et al 2008;Liu and Tay 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The recovery rate, concentrate grade and separation efficiency are selected as the main indicators to evaluate the separation results (Raj et al 2013;Uan et al 2013;Uma Rani et al 2013). The separation efficiency could be calculated as Eq.…”
Section: Particle Size Distribution Of the Crushing Waste Pcb Slotsmentioning
confidence: 99%